Assessing the importance of the Indonesian plastic waste imports to industrial growth and the environment - Krisna Gupta; Biyan Shandy Paramayudha (Center for Indonesian Policy Studies (CIPS), 2024)
The impact of international trade is often associated with economic development, especially for emerging markets. However, under conditions like negative externalities, trade can have negative consequences. Research on the impact of trade on the environment is still lacking despite its recent emergence. In this paper, we examine the relationship between trade, the environment, and industrial development, specifically in the plastic waste trade. We examine a sudden relaxation of a plastic waste import ban in Indonesia and try to link it with the development of Indonesian recycling industries and other plastic waste importing industries more generally. We find little evidence to suggest that importing plastic waste benefits Indonesia. Moreover, since importing plastic waste is not followed by investment in the recycling industry, it is plausible that most of this plastic waste goes untreated. Not only this policy brings no benefit to Indonesia, it is also not in line with the notion that the developed countries, which are the biggest source of the Indonesian plastic waste, export their plastic waste to be recycled in developing countries.
Keywords: F13; Q56; 330; plastic waste; international trade; economic development; environment; plastics; waste; imports; environmental impact; economic growth; industrialization; Indonesia